Occurrence of Aeshna viridis in marsh ditches in relation to habitat conditions (Odonata: Aeshnidae). Issue 3 (3rd July 2018) - Kastner, Friederike; Buchwald, Rainer; Biedermann, Robert
Abstract : Habitat loss and fragmentation induce a decline and endangerment of freshwater organisms such as Aeshna viridis, an endangered dragonfly species characterised by a specific insect–plant association to the macrophyte Stratiotes aloides . In order to implement conservation measures, a good level of knowledge about the occurrence, habitat requirements and quality, as well as patch size of the species is important. We analysed the influence of several habitat parameters on the presence/absence and abundance of A. viridis exuviae using habitat models (generalised linear mixed-effect models). The ditches populated by A. viridis were classified as moderately polluted and meso- to eutrophic with a high cover of emerged S. aloides stands. The main factor contributing to the presence of A. viridis was the coverage of emerged S. aloides combined with the ditch width. The 90% probability of the presence of A. viridis was achieved at a cover of 14% (8.4 m²) and/or 77% (46.2 m²) of emerged S. aloides . The number of A. viridis exuviae was positively affected by the cover of emerged S. aloides and negatively affected by the sediment thickness, water maintenance and water temperature in March and August. The habitat parameters – water temperature and sediment thickness – are associated with S. aloides in the beginning of siltation of ditch succession. If ditch cleaning takes place during larvae development, eggs and larvae are removed by these procedures. In an optimal situation, the S. aloides populations occur in a mosaic of different states of siltation, which is managed by adapted water maintenance.